Hubungan Manajemen Kelas dan Motivasi Belajar dengan Mutu Pembelajaran di UPT SDN 238 Ujung Tanah Kecamatan Mare Kabupaten Bone - Jusfiani; Wahira; Amir Pada (PT PUSTAKA CENDEKIA GROUP, 2025)
The formulation of the problem in this study is how is the description of class management, learning motivation, and learning quality at UPT SDN 238 Ujung Tanah, Mare District, Bone Regency? and is there a significant relationship between class management and learning motivation with the quality of learning at UPT SDN 238 Ujung Tanah, Mare District, Bone Regency? This study is a correlation study that aims to determine the description of class management, learning motivation, learning quality and the relationship between class management and learning motivation with the quality of learning at UPT SDN 238 Ujung Tanah, Mare District, Bone Regency. The research approach is a quantitative approach. Research data were obtained through questionnaires and documentation. The population in the study were all high-class students at UPT SDN 238 Ujung Tanah, Mare District, Bone Regency, totaling 30 students. The sample in the study amounted to 30 students. The data analysis technique was descriptive and inferential statistical analysis. The results obtained in this study are a description of class management showing a very high category and learning motivation showing a very high category with learning quality showing a very high category and class management and learning motivation have a significant relationship to the quality of student learning, especially in the high class of UPT SDN 238 Ujung Tanah, Mare District, Bone Regency.